Towards an integrative bioinformatic and bibliometric analysis of C23/NCL post-translational modifications diversity. data curation by implications on molecular size, folding, trafficking, interactions, functions and unconventional secretion - Asensio, Cristian Jorge Alejandro (2022)
C23/NCL has multiple domains, PTMs, polyanionic stretches, repeats, functions and subcellular locations and without signal peptide is enriched on cancer cells surface acting as co-receptor, alarmin, etc. Its study is also difficulted by lack of full-length C23 expression in bacteria. C23 integrates multiple aspects of DNA and RNA metabolism and cell cycle/metabolism and senses environmental cues in cell surface, cytosol and nucleus. Its diverse PTMs coordinate interactions with proteins, nucleic acids, carbohydrates, cations, LPS and lipids as well as the trafficking from nucleolus to nucleoplasm, cytosol, microtubules, vesicles, membrane and back again. It is unconventionally secreted, clustering on membranes with receptors, extracellular factors, matrix, cations and pathogens. Most steps on its trafficking, interaction partners, or if the diverse PTMs are hierarchical and/or alternative are unclear. Understanding mechanisms should help testing anti-C23 drugs to prevent viruses/bacteria entry, to target cancer and for diagnostics. Articles have dispersed on different roles and cells, so bibliometric/bioinformatic approaches might help better in making sense on PTMs diversity. Thus, we aimed to recollect C23 PTMs from several databases, curating data by impacts on subcellular location, functions/interactomes, frequency, etc. We detected ~180 PTMs (some alternative) involving phosphoryl, acetyl, succinyl, ubiquitin, sumo, glycosyl, NO and methyl groups plus cleavage. Enzyme crosstalk data and 7 known PTMs were absent. We conclude that a curated PTM database might help in experiment and drug design and in knowledge gap identification. Studies are needed on: a) expansion of sequence/folding diversity by cleavage, isomerization, oligomerization and charge density, b) finding PTMs in cytosolic C23 as markers of shuttling to or from membranes, c) interaction motif identification, d) modeling impacts on folding, e) searching any PTM-code and epigenetic/signaling roles.